Peningkatan Efisiensi dan Produksi Pangan dengan Pembangunan Sistem Irigasi Pipa di Tingkat Tersier - M Yanuar J Purwanto; Erizal Erizal; Nova Anika (Jurnal Irigasi, 2012)
Pipe Irrigation system can be one solution in improving irrigation efficiency. It will has impact on food production due to more planted areas. In addition, pipe irrigation can control distribution water effectively by installing measurement devices. Another advantage is the integration structure between pipe and farm road by setting pipe network system under the farm road, can be used for farm equipment and agricultural machinery operation. The purpose of this study were 1) To see the urgency of pipe irrigation in irrigated paddy field, 2) Find the benefit of integrated infrastructure development in the irrigated paddy field. This study located in the Cihea Irrigation System, Cianjur, West Java with total area 5484 ha. Adoption of integrated package infrastructure was evaluated and pipe irrigation was Constructed in Tertiery level. The stufy was conducted using a dynamic model. An dynamic simulation was done to evaluate rice production conditions (existing) and conditions with the construction of irrigation pipe. The results showed that if maintaining the existing infrastructures condition, food production will continue to decline from year to year due to lack of irrigation efficiency improvements and Cropping Intencity will also decrease due to conversion of productive land. However, the construction of irrigation pipe will increase rice production. Under the current model, Adoption of integrated infrastructure development in the Cihea Irrigation with pipe density about 50 m/ha will increase production by 22.19% by 2020.